Pesantren as the Pivot of Islamic Higher Education Science Development - Irpani, Ayit (AIM: Journal of Islamic Education Management, 2024)
Pesantren have historically served as the backbone of traditional Islamic education in Indonesia. As Islamic higher education continues to evolve, pesantren institutions are increasingly recognized for their foundational role in shaping academic and spiritual development. This study uses a historical-analytical approach to trace the evolution of pesantren into a core component of Islamic higher education, examining philosophical, curricular, and institutional changes over time. Findings show that pesantren not only maintain traditional Islamic values but also adapt their curriculum to align with contemporary educational standards. Their educational philosophy—centered on spiritual growth, discipline, and community engagement—has significantly influenced the identity formation and independence of students. Moreover, several pesantren have successfully transformed into higher education institutions, integrating modern disciplines while preserving core Islamic teachings. Despite their progress, pesantren face challenges such as curriculum standardization, accreditation demands, and institutional autonomy. However, strategic collaborations with universities and state recognition have opened new opportunities for pesantren to contribute meaningfully to national education. The study emphasizes that pesantren remain vital to the development of Islamic higher education in Indonesia. Enhanced cooperation between pesantren and Islamic universities offers promising pathways for integrated, value-based education.